The proteasome inhibitor Velcade enhances rather than reduces disease in mouse hepatitis coronavirus-infected mice - Raaben, Matthijs; Grinwis, Guy C M; Rottier, Peter J M; de Haan, Cornelis A M (Journal of virology, 2010)
Many viruses, including coronaviruses (CoVs), depend on a functional cellular proteasome for efficient infection in vitro. Hence, the proteasome inhibitor Velcade (bortezomib), a clinically approved anticancer drug, shown in an accompanying study (M. Raaben et al., J. Virol. 84:7869-7879, 2010) to strongly inhibit mouse hepatitis CoV (MHV) infection in cultured cells, seemed an attractive candidate for testing its antiviral properties in vivo. Surprisingly, however, the drug did not reduce replication of the virus in mice. Rather, inhibition of the proteasome caused enhanced infection with lethal outcome, calling for caution when using this type of drug during infection.